(untitled) (Prakriti - The International Multidisciplinary Research Journal, 2025)
This study examined the spatio-temporal dynamics of canal irrigation in Bhiwani District from 1980-81 to 2020-21. By analyzing intra-block variations, the research identified trends in canal irrigation expansion and its impact on agricultural productivity. The findings revealed a consistent increase in canal irrigation, with significant disparities among blocks due to geographical, infrastructural, and climatic factors. The study highlighted the role of government interventions and water management practices in improving irrigation coverage. The study also explored how the availability of canal irrigation influenced cropping patterns and yield improvements in different blocks. It assessed the socio-economic impact of irrigation on farmers, highlighting the correlation between improved water access and agricultural income. Additionally, the research investigated challenges such as water scarcity, maintenance issues, and the need for modernization in canal irrigation systems. Moreover, the analysis provided insights into the effectiveness of past and current government policies in promoting canal irrigation. The study underscored the importance of integrating advanced technologies such as remote sensing and GIS for better water management. Recommendations for sustainable water resource utilization and policy interventions were presented to ensure long term agricultural viability in the district. Canal irrigation played a vital role in supporting agriculture, particularly in semi-arid regions such as Bhiwani District, Haryana. This study provided a spatio-temporal analysis of canal irrigation across different blocks within the district, examining changes over four decades from 1980-81 to 2020-21. The research evaluated the impact of irrigation expansion on agricultural productivity, highlighting the disparities caused by geographical and infrastructural factors. Findings indicated a steady increase in canal irrigation, improving crop yields and reducing reliance on erratic rainfall. However, challenges such as inefficient water distribution, infrastructure maintenance, and climate change effects persisted. The study emphasized the need for sustainable water management policies, technological advancements in irrigation, and government interventions to ensure long-term agricultural sustainability and equitable water access.